2015
DOI: 10.14434/pders.v34i1.13918
|View full text |Cite
|
Sign up to set email alerts
|

School Performance and Disease Interference in Adolescents with Sickle Cell Disease

Abstract: Sickle cell disease (SCD) results in neuropsychological complications that place adolescents at higher risk for limited educational achievement. A first step to developing effective educational interventions is to understand the impact of SCD on school performance. The current study assessed perceptions of school performance, SCD interference and acceptability of educational support strategies in adolescents with SCD. To identify potential risk factors, the relationship between school performance, SCD interfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…Provision of support in some NEIs was situational rather than systemic, depending largely on the individual lecturer. Similarly, Gelbar et al ( 2015 ) found that support for SWDs was left to the discretion of lecturers and that students’ experience of this was ‘feeling left behind’. One explanation for the lack of support could be educators’ lack of understanding or training in disability and support measures (Mosia & Phasha 2017 ).…”
Section: Resultsmentioning
confidence: 98%
“…Provision of support in some NEIs was situational rather than systemic, depending largely on the individual lecturer. Similarly, Gelbar et al ( 2015 ) found that support for SWDs was left to the discretion of lecturers and that students’ experience of this was ‘feeling left behind’. One explanation for the lack of support could be educators’ lack of understanding or training in disability and support measures (Mosia & Phasha 2017 ).…”
Section: Resultsmentioning
confidence: 98%
“…These findings support what has previously been described in studies with adolescents and adults with SCD. These include difficulties in developing peer relationships; limitations in physical activity; school and activity absenteeism; feelings of worry and uncertainty; disease-related stigma; and negative responses from peers, teachers, and HCPs [3,4,25-32]. These challenges were described by participants in the context of Ontario, Canada, and highlight the continued perceived challenges this population faces throughout childhood and adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…In line with neurocognitive deficits, academic underachievement is common for children with SCD 9,18,19 . Approximately 60% of children with SCD report academic difficulties related to their disease 20 . Academic deficits in SCD are associated with overt and silent stroke 13,18,21 , and school absenteeism 22,23 .…”
Section: Introductionmentioning
confidence: 99%